Mapping of quantitative trait loci and mining of candidate genes for seed viability in soybean [Glycine max (L.) Merr.] - Saini, Manisha; Yadav, Raju R.; Kumar, Rahul; Chandra, Subhash; Rathod, N. Krishna Kumar; Taku, Meniari; Yadav, Manu; Basu, Sudipta; Rajendran, Ambika; Lal, S. K.; Talukdar, Akshay (Frontiers in Plant Science, 2025)
Global oilseed crop soybean [Glycine max (L.) Merrill] contains 18%–20% oil, 40%–45% protein, and countless nutrients vital for human health. It is grown worldwide for food, feed, pharmaceutical, and industrial applications. However, inherent loss of seed viability during ambient storage poses serious bottleneck in the production and maintenance of quality seeds. Understanding inheritance and mapping of quantitative trait loci (QTLs) for seed viability would help in designing breeding program for developing varieties with higher viability of the seeds. In this study, attempt was made to map QTLs and identify candidate genes for seed viability in soybean. A high-viable genotype EC1023 (>90% germination after 1 year of storage) was hybridized with VLS61, a poor storing genotype (<70% germination after 1 year of storage), and the F1 seeds were advanced to the next generation. The F2:3 seeds were subjected to accelerated ageing (AA) by exposing it to 41°C at 100% RH for 72h followed by viability testing through germination test. After AA test, the germination of the parental genotypes EC1023 and VLS61 were 40% and 14%, respectively, and that of the F2:3 seeds ranged from 4.16% to 71.42% indicating wide variability in the viability of the seeds. Genetic polymorphism studied with 517 SSR markers indicated the polymorphism between the parental genotypes to be 20.35%; however, distribution of the polymorphism was not uniform across the chromosomes; Chr. 14 had 30.00% polymorphism as against 7.14% on Chrs.12. Through inclusive composite interval mapping approach, 8 QTL for seed viability, namely, qSv-6.1 and qSv-6.2, qSv-7.1, qSv-8.1, and qSv-8.2, qSv-10.1, qSv-13.1, and qSv-17.1 were mapped on Chrs. 6, 7, 8, 10, 13 and 17, respectively. The phenotypic variation explained (PVE) by the QTL were 1.97%–11.10%. Two QTL, namely, qSv-7.1 (PVE = 11.10%) and qSv13.1 (PVE = 11.08%) appeared to be major QTLs for seed viability and rest minor ones. All QTL except qSv8.2 appeared to be novel. The mapped QTLs were validated in 40 inter-specific RILs with varying level of seed viability. The SSR marker Satt538 linked to the QTL qSv8.2 could successfully (70%) separate the highly viable RILs from the poor-viable RILs. Similarly, SSR markers Sat_316 and Sat_173 were 80%–85% successful in separating the high and poor viable RILs. Based on Protein Analysis Through Evolutionary Relationships (PANTHER), gene annotation information, and literature search, more than 500 candidate genes for seed viability underlying the mapped QTL were identified. The mapped QTL and the identified candidate genes will pave the way for marker-assisted breeding of soybean to generate genotypes with improved seed viability.